2013
DOI: 10.1515/hf-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of oven-dry density of wood by time-domain terahertz spectroscopy

Abstract: Wood is relatively transparent to terahertz (THz) radiation with wavelengths in the submillimeter range. This radiation has a high potential for sensing and imaging wood with a good spatial resolution. THz is especially sensitive to moisture content, fiber alignment, and density – all of which are critical in the manufacturing of wood products. In this work, a systematic study was undertaken on 46 very different wood species by means of THz time-domain spectroscopy with density determination in focus. The diel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Wood is an extremely complex material and variances in its structure (e.g., hardwoods vs softwoods) will result in different densities between species and within the same species. The densities of 46 different species of wood have been determined by Inagaki et al using a MaxwellGarnet effective medium theory based on cylindrical geometry [59]. They found that this model agreed well with the measured densities obtained by using the oven-dry weight and volume measurements.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Wood is an extremely complex material and variances in its structure (e.g., hardwoods vs softwoods) will result in different densities between species and within the same species. The densities of 46 different species of wood have been determined by Inagaki et al using a MaxwellGarnet effective medium theory based on cylindrical geometry [59]. They found that this model agreed well with the measured densities obtained by using the oven-dry weight and volume measurements.…”
Section: Resultsmentioning
confidence: 74%
“…The index of refraction can be used to compute the dielectric constant of the wood , which is correlated with the density of the wood sample [59] . Wood is an extremely complex material and variances in its structure (e.g., hardwoods vs softwoods) will result in different densities between species and within the same species.…”
Section: Resultsmentioning
confidence: 99%
“…According to Duvillaret et al, the measured signal is very small compared to the noise level at low frequencies [38], which results in a phase that may not go to zero at zero frequency as must physically happen. The distorted phase at the low frequency points is linearly extrapolated [39] to account for this, and implemented in the analysis conducted in the experiments that follow.…”
Section: Phase Unwrappingmentioning
confidence: 99%
“…There have been several reports on the interaction of THz radiation with wood [5,14,38,[48][49][50][51], which have highlighted applications of THz radiation to the wood products industry, including density mapping [5], defect detection [14], properties of paper [52] and wood-plastic composites [53], dendrochronology [6], and sensitivity to internal moisture suitable for imaging of MC [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation